A low-power conditional analog correlated multiple sampling circuit for low-noise CMOS image sensor. (May 2022) - Xu, Jiangtao; Wei, Jiahao; Chen, Quanmin; Zha, Wanbin; Nie, Kaiming
Abstract: This paper presents a low-power conditional analog correlated multiple sampling (CACMS) circuit based on the passive switched-capacitor (SC) correlated multiple sampling (CMS) technique. The bright pixel output noise is dominated by photon shot noise, which cannot be reduced by CMS within one readout. Therefore, in the CACMS, the CMS operation is performed for a dark pixel output and turned off for a bright pixel output. As a result, the power consumption of the CACMS circuit under the bright pixel output is reduced by 28%. The transfer function and noise reduction effect of the CACMS circuit are also analyzed. The simulation results show that the CACMS circuit achieves an input-referred random noise of 70.3μVrms . In addition, the proposed SC CMS scheme provides designers with a free trade-off on the number of capacitors and the readout time. In the CACMS, the readout time of the SC CMS circuit is reduced by 16.7% at the cost of an extra capacitor.